2015
DOI: 10.1002/chem.201500998
|View full text |Cite
|
Sign up to set email alerts
|

Merger of Visible Light Induced Oxidation and Enantioselective Alkylation with a Chiral Iridium Catalyst

Abstract: A single chiral octahedral iridium(III) complex is used for visible light activated asymmetric photoredox catalysis. In the presence of a conventional household lamp and under an atmosphere of air, the oxidative coupling of 2-acyl-1-phenylimidazoles with N,N-diaryl-N-(trimethylsilyl)methylamines provides aminoalkylated products in 61-93 % yields with high enantiomeric excess (90-98 % ee). Notably, the iridium center simultaneously serves three distinct functions: as the exclusive source of chirality, as the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 76 publications
1
40
0
2
Order By: Relevance
“…Its application in organic synthesis has therefore expanded rapidly during the past decades (1), most recently in the context of enantioselective photoredox catalysis with transition metals (2,3,4). With several recent noteworthy exceptions, each of which involves the α-functionalization of carbonyl compounds by a chiral iridium catalyst (5,6,7), the metal-catalyzed methods require two catalysts, a transition metal complex that undergoes photoexcitation and serves as a site for redox chemistry, as well as a separate chiral catalyst that effects enantioselective bond formation. Transition metal-free asymmetric photoredox catalysis has also been reported (8,9).…”
mentioning
confidence: 99%
“…Its application in organic synthesis has therefore expanded rapidly during the past decades (1), most recently in the context of enantioselective photoredox catalysis with transition metals (2,3,4). With several recent noteworthy exceptions, each of which involves the α-functionalization of carbonyl compounds by a chiral iridium catalyst (5,6,7), the metal-catalyzed methods require two catalysts, a transition metal complex that undergoes photoexcitation and serves as a site for redox chemistry, as well as a separate chiral catalyst that effects enantioselective bond formation. Transition metal-free asymmetric photoredox catalysis has also been reported (8,9).…”
mentioning
confidence: 99%
“…At the same time, this iridium enolate represents the key intermediate of the catalytic cycle by reacting with the reductively generated electron-deficient radicals in a stereocontrolled fashion. We subsequently demonstrated that these iridium complexes also catalyze photooxidative enantioselective a-aminoalkylations in air [47] and asymmetric radical/radical couplings [48] that are initiated by photoinduced electron transfer. In both cases, a single catalyst was sufficient for both the photoredox chemistry and the asymmetric catalysis.…”
Section: Dual Chiral Lewis Acid/photoredox Catalystsmentioning
confidence: 99%
“…[53] Als Alkylierungsreagentien wurden Benzyl-und Phenacylbromide sowie a-Silylamine eingesetzt. [53] Als Alkylierungsreagentien wurden Benzyl-und Phenacylbromide sowie a-Silylamine eingesetzt.…”
Section: Angewandte Chemieunclassified